Scalable Molten Salt Synthesis of Platinum Alloys Planted in Metal–Nitrogen–Graphene for Efficient Oxygen Reduction - Zaman, Shahid; Su, Ya‐Qiong; Dong, Chung‐Li; Qi, Ruijuan; Huang, Lei; Qin, Yanyang; Huang, Yu‐Cheng; Li, Fu‐Min; You, Bo; Guo, Wei; Li, Qing; Ding, Shujiang; et al. (Angewandte Chemie International Edition, 2022)
Fuel cells are considered as a promising alternative to the existing traditional energy systems towards a sustainable future. Nevertheless, the synthesis of efficient and robust platinum (Pt) based catalysts remains a challenge for practical applications. In this work, we present a simple and scalable molten‐salt synthesis method for producing a low‐platinum (Pt) nanoalloy implanted in metal–nitrogen–graphene. The as‐prepared low‐Pt alloyed graphene exhibits a high oxygen reduction activity of 1.29 A mgPt−1 and excellent durability over 30 000 potential cycles. The catalyst nanoarchitecture of graphene encased Pt nanoalloy provides a robust capability against nanoparticle migration and corrosion due to a strong metal–support interaction. Similarly, advanced characterization and theoretical calculations show that the multiple active sites in platinum alloyed graphene synergistically account for the improved oxygen reduction. This work not only provides an efficient and robust low‐Pt catalyst but also a facile design idea and scalable preparation technique for integrated catalysts to achieve more profound applications in fuel cells and beyond. Pt−Co nanoalloys planted in the metal–nitrogen–graphene system achieved by a scalable molten salt pyrolysis method demonstrate improved activity and stability for oxygen reduction through a synergistic effect among multiple active sites and a strong metal–support interaction.